Answer :

Put x = cos θ


= sin–1(2tan–1)


1 – cosθ = 2 sin2 and 1 + cos θ = 2 cos2


= sin–1(2tan–1)


= sin–1(2tan–1)


= sin–1(2tan–1(tan))


= sin–1()


= sin–1(θ)


But θ = cos–1x


The above expression becomes sin–1(cos–1x)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers